THE ROLE OF PERSIAN LANGUAGE LEARNING IN DEVELOPING INTERCULTURAL COMMUNICATIVE COMPETENCE - Norqobilov Farruh; G`ulomjonov Barkamol (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This paper explores the influence of Persian language learning on the development of intercultural communicative competence among university students. Drawing on classroom observations and learner reflections, the study highlights how exposure to Persian culture, literature, and language structure fosters awareness of cultural diversity and improves learners' ability to communicate across cultures. The findings suggest that Persian language instruction, particularly in regions with historical and cultural ties to Iran, provides a unique opportunity for students to expand their worldview and develop deeper linguistic sensitivity.